Reconstruction of Through-and-through Oromandibular Defect: Comparison of Four Different Techniques. (February 2017) - Wu, John Chung-Han; Lee, Yi-Chieh; Cheng, Yu-Chun; Wu, Chih-Wei
Abstract : Background: Through-and-through oromandibular defects originate from surgical intervention of tumors of the oral cavity involving external skin, soft tissue, bone, and oral lining. Reconstruction of such composite defects is primarily achieved by 4 methods using distinct flaps in Chang Gung Memorial Hospital, including a single anterolateral thigh (ALT) flap, a single fibula flap, an osteomyocutaneous peroneal artery-based combined flap, and a combination of a fibular flap and an ALT flap, also known as a double flap. Methods: In this retrospective study, 41 patients with through-and-through oromandibular defects reconstructed in Chang Gung Memorial Hospital Linkou branch from July 2007 to June 2009 using either of the 4 flaps were evaluated. Patients were divided into 4 groups according to the choice of flap, and their surgical outcomes, immediate and late complications, and their general condition were studied. Group 1 included 12 patients reconstructed with a single ALT flap, whereas group 2 included 15 patients using fibular flaps. Group 3 included 8 patients with osteomyocutaneous peroneal artery-based combined flaps, and group 4 included 6 patients who underwent reconstruction with double flaps. Results: Among all statistical results, we found that none of the differences regarding either patient demography or surgical outcomes between groups were statistically significant, except for squamous cell carcinoma staging. Conclusions: Although the results were insignificant, trends within the data could be seen that support previous notions regarding each reconstruction method. For future studies, we strongly recommend a larger sample size.